2022
DOI: 10.1055/a-1887-7645
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Risk Factors for Breast Skin Necrosis following Autologous versus Device-Based Breast Reconstruction

Abstract: Background: Mastectomy skin flap necrosis often necessitates prolonged wound care, surgical re-excision, and increases the risk for infection. This study aims to compare rates of skin flap necrosis between autologous and device-based reconstructions and identify risk factors. Methods: The authors retrospectively identified patients who underwent immediate breast reconstruction using either the deep inferior epigastric perforator flap (n = 373 breasts, 41 percent) or tissue expanders (n = 529 breasts, 59 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This finding was consistent with numerous prior studies that have correlated mastectomy skin necrosis with BMI > 30 kg/m 2 . [51][52][53][54] While perfusion of distal mastectomy flap skin is primarily dependent on native breast anatomy and extirpative technique, reconstructive surgeons can optimize outcomes by minimizing additional challenges to skin perfusion and anticipating potential wound healing problems. To this end, it has been our preference to offer immediate autologous reconstruction to almost all obese patients undergoing nipple-or skinsparing mastectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was consistent with numerous prior studies that have correlated mastectomy skin necrosis with BMI > 30 kg/m 2 . [51][52][53][54] While perfusion of distal mastectomy flap skin is primarily dependent on native breast anatomy and extirpative technique, reconstructive surgeons can optimize outcomes by minimizing additional challenges to skin perfusion and anticipating potential wound healing problems. To this end, it has been our preference to offer immediate autologous reconstruction to almost all obese patients undergoing nipple-or skinsparing mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be mentioned that in a recent study, Lu Wang et al determined that immediate autologous reconstruction did not independently increase the risk of mastectomy skin necrosis relative to device-based methods. 54 Prior studies have reported detrimental effects of obesity on efficiency metrics in autologous breast reconstruction. 14 In two studies comparing obese to nonobese patients undergoing abdominal free flap breast reconstruction, mean operative times were found to be significantly longer among the obese cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation